Erratum - Erratum (Iranian Endodontic Journal, 2025)
In the article titled Revascularization of a Previously Treated Mandibular First Molar with Open Apices: A Case Report by Mojgan Feli, Anita Taheri and Mahgol Mehrabani, published in the Iranian Endodontic Journal [2024;19(2):120-123; doi: 10.22037/iej.v19i2.43321], the authors regret an omission in the acknowledgment section of the original publication.